Increased intake of health-promoting foods as a benefit of the exclusion of gluten and casein from the diet of ASD patients - Hozyasz, Kamil; Jessa, Justyna (Progress in Nutrition, 2023)
The high intake of nuts, seeds, berries and cruciferous vegetables has beneficial effects on the immune system, as well as communication skills and behaviour. Gluten- and/or casein-free diets are the most common interventions in ASD patients; however, scientific evidence for their use is poor. Previous research has not yet examined the effect of the change in the frequency of consumption of nuts, seeds, berries and cruciferous vegetables following the implementation of elimination diets in ASD children. A sample of 88 ASD patients and their mothers was followed for 12 months after making their free choice of a gluten-free diet, a gluten- and casein-free diet or a regular diet. Children with ASD on a gluten- and casein-free diet have significantly higher intake of seeds, berry fruits and cruciferous vegetables than controls, while patients on a gluten-free diet consumed more frequently seeds and cruciferous vegetables. In both groups, after dietetic intervention, the frequency of nut consumption tended to be higher than in patients on a regular diet. Unflagging interest and frequently reported subjective feelings of improvement in parents of autistic children on elimination diets may be due to the healthy balance of modified diets and their multidirectional impact.